Study of Antioxidant Activities from Antihypertension Drug Plant of the Indralaya Area - Seni Metasari; Muharni Muharni; Elfita Elfita; Heni Yohandini (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2020)
Ogan ethnic population in Indralaya, Ogan Ilir District, South Sumatra was known to have used several types of plants, there are Swietenia mahagoni, Averrhoa carambola, Syzygium samarangense, Musa acuminata, Nymphaea rubra, Syzygium polyanthum, and Andrographis paniculata for the treatment of hypertension. But, scientific information has not yet been found secondary metabolites that are responsible for providing these activities. The study began with the extraction of methanol from the seven types of plants using methanol as a solvent. Each thick extract was tested for its activity using the 1,1-diphenyl-1-picryllhydrazyl (DPPH) method. The extract which showed the highest activity (methanol extract) was subsequently carried out in vitro antihypertension test using the Angiotencyn Converting Enzyme (ACE) method. Antioxidant test results showed that the methanol extract from S. samarangense stem bark had the highest antioxidant activity with IC50 was 83.06 μg/mL. Antihypertension test of methanol extract from S. samarangense stem bark obtained IC50 ACE was 61.56 μg/mL. Based on the IC50 value, it shows that S. samarangense stem bark has potential as a source of antioxidant compounds as well as a source of antihypertension compounds. Keywords: Syzygium samarangense, stem bark, antioxidant, antihypertension